Culinary Students' Perception toward Teaching and Practical Learning Process - Noor Fatasha Mohd Fauzi,; Md Sahak, Adibah Aishah; Abdul Wafi Abdul Rahman,; Noorzetty Fazrina Mohamad Dzoha, (Research and Innovation in Technical and Vocational Education and Training, 2024)
An effective practical teaching and learning process (PdP) can be created if lecturers and students are highly motivated, efficient and have skills in the field they are engaged in. Therefore, the purpose of this study is to identify the perception of culinary students on the equipment and hardware factors, safety and lecturers' teaching during the practical PdP process in the kitchen. The design of this study is a quantitative study and the method used in this study is a survey method. By using a set of questionnaires used as a data collection tool. The collected data were analyzed using SPSS software version 26, as well as to identify the frequency, mean percentage and standard deviation. A total of 92 Culinary Arts Diploma students at KYPJ were involved as study respondents. Overall, the findings of the study show that the perception of culinary students towards the factors of equipping equipment and hardware, safety and lecturers' teaching in the practical PdP process in the kitchen is high, although some things need to be improved on the factors that affect the practical PdP process in the kitchen. In conclusion, the factors of equipping equipment and hardware, safety and strong teaching by lecturers influence the practical PdP process in the kitchen at KYPJ bringing a positive impact to culinary arts students